Determinants of Profitability in Aviation Industry of Europe and America - Alexandros Garefalakis; George Mantalis; Christos Lemonakis; Konstantinos Vassakis; konstantinos Spinthiropoulos (International Journal of Supply Chain Management, 2016)
The civil aviation, is an industry evolving at exponential speed despite the significant problems that faces in the last decade (increase of oil price, terrorist attacks etc.) An important feature of aviation firms and generally all companies, is that their size reflects their efficiency and in general their economic growth. In this era of financial crisis, liquidity is a significant factor for the stabilization and growth of economic organizations. Therefore, the examination of cash flows as indicator of liquidity limitations is necessary for the measurement of firms profitability. In this study, we tried to see whether the efficiency of size of European and American airlines listed firms, depends on their growth and cash flows from investment activity